Determinants of Green Innovation Culture on the Success of Green Human Resource Management: Study on Manufacturing Companies in West Java, Indonesia - Arifin, Yusuf (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
This study aims to analyze the determinants of green innovation culture on the successful implementation of Green Human Resource Management (Green HRM) in environmentally oriented manufacturing organizations. A quantitative research design was employed through a survey of 210 respondents (HR managers and staff) from green manufacturing firms in West Java. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results demonstrate that green innovation culture has a significant influence on the success of Green HRM (β = 0.62; p < 0.001). The most dominant dimensions identified were green creativity and sustainable orientation. These findings suggest that green innovation culture is a key factor driving the effectiveness of Green HRM. The implications highlight the need for organizations to cultivate values, norms, and work practices that are oriented toward sustainable innovation.